Islamic Boarding School Alumni Network in the Development of Islamic Religious Education in Meranti Islands Regency - Chanifudin, Chanifudin; Tekwana, Peryoly (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This study aims to examine the Alumni Network of Islamic Boarding Schools in the development of Islamic religious education in the Meranti Islands Regency. This type of research is descriptive qualitative research that focuses on the alumni network of Islamic boarding schools in developing Islamic religious education, especially in the Meranti Islands Regency, and then presents and describes it as it is. The population in this study is alumni of Islamic boarding schools who are members of the BKAPP Organization using data collection techniques using interviews and documentation. The analysis technique in this study uses data triangulation. The results of the study show that the establishment of BKAPP is a form of real alumni service to teachers, society, and the state as a form of totality to be human, humanized, and humanized and as a foundation in developing Islamic religious education in Meranti Islands Regency. The Islamic boarding school alumni network comprises not only Islamic boarding school alumni but also the community. This makes the BKAPP alumni organization unique and different from alumni organizations. The contribution of Islamic boarding school alumni can be seen in existing Islamic boarding school educational institutions. The existence of Islamic boarding school alumni motivates the community to race against each other and make education important.